1998
DOI: 10.1091/mbc.9.9.2561
|View full text |Cite
|
Sign up to set email alerts
|

Rho and Rab Small G Proteins Coordinately Reorganize Stress Fibers and Focal Adhesions in MDCK Cells

Abstract: The Rho subfamily of the Rho small G protein family (Rho) regulates formation of stress fibers and focal adhesions in many types of cultured cells. In moving cells, dynamic and coordinate disassembly and reassembly of stress fibers and focal adhesions are observed, but the precise mechanisms in the regulation of these processes are poorly understood. We previously showed that 12-O-tetradecanoylphorbol-13-acetate (TPA) first induced disassembly of stress fibers and focal adhesions followed by their reassembly i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

17
90
0

Year Published

1999
1999
2010
2010

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 95 publications
(107 citation statements)
references
References 42 publications
(63 reference statements)
17
90
0
Order By: Relevance
“…At 16 h, the staining of E-cadherin at the cell-cell adhesion sites became indistinct and most cells scattered (Figure 4g). These results are consistent with the previous observations (Ridley et al, 1995;Imamura et al, 1998). Stimulation of sMDCK-RacDA-1 cells with HGF/SF for 16 h caused slight spreading of the cells and weaker staining of E-cadherin at the cell-cell adhesion sites (Figure 4h).…”
Section: Increased Accumulation Of E-cadherin and B-catenin At Cell-csupporting
confidence: 93%
See 4 more Smart Citations
“…At 16 h, the staining of E-cadherin at the cell-cell adhesion sites became indistinct and most cells scattered (Figure 4g). These results are consistent with the previous observations (Ridley et al, 1995;Imamura et al, 1998). Stimulation of sMDCK-RacDA-1 cells with HGF/SF for 16 h caused slight spreading of the cells and weaker staining of E-cadherin at the cell-cell adhesion sites (Figure 4h).…”
Section: Increased Accumulation Of E-cadherin and B-catenin At Cell-csupporting
confidence: 93%
“…We previously showed that TPA also induced disruption of cell-cell adhesion, followed by cell migration in MDCK cells (Takaishi et al, 1995;Imamura et al, 1998). We furthermore showed that TPA did not disrupt the cell-cell adhesion at least for 2 h stimulation in sMDCK-RacDA-1 cells (Imamura et al, 1998). We next examined the e ects of HGF/SF and TPA on cell-cell adhesion and cell migration of sMDCK-RacDA-1 and -Cdc42HsDA-1 cells for 16 h stimulation.…”
Section: Increased Accumulation Of E-cadherin and B-catenin At Cell-cmentioning
confidence: 90%
See 3 more Smart Citations